DETERMINASI KEPUTUSAN PEMBELIAN PADA KONSUMEN PRODUK DISTRO DI KOTA MEDAN - AULIA ARIEF NASUTION (JURNAL ILMIAH KOHESI, 2023)
This study aims to examine the influence of Celebrity Endorse, Social Environment and Electronic Word of Mouth on Purchasing Decisions. This research uses a type of causality research. The research population is 150 distro consumers in Medan City. Determination of the number of samples using the slovin method so that a total sample of 109 people was found, sampling using simple random sampling. The data analysis technique uses multiple linear regression analysis using the SPSS application. The results of this study indicate that celebrity endorsements and electronic word of mouth have a positive and significant effect on purchasing decisions. While the social environment has no significant effect on purchasing decisions.